Sub-critical water as a green solvent for production of valuable materials from agricultural waste biomass: A review of recent work - A. Shitu; S. Izhar; T. M. Tahir (Global Journal of Environmental Science and Management)
Agricultural waste biomass generated from agricultural production and food processing industry are abundant, such as durian  peel, mango peel, corn straw, rice bran, corn shell, potato peel and many more. Due to low commercial value, these wastes are disposed in landfill, which if not managed properly may cause environmental problems. Currently, environmental laws and regulations pertaining to the pollution from agricultural waste streams by regulatory agencies are stringent and hence the application of toxic solvents during processing has become public concern. Recent development in valuable materials extraction from the decomposition of agricultural waste by sub-critical water treatment from the published literature was review. Physico-chemical characteristic (reaction temperature, reaction time and solid to liquid ratio) of the sub-critical water affecting its yield were also reviewed. The utilization of biomass residue from agriculture, forest wood production and from food and feed processing industry may be an important alternative renewable energy supply. The paper also presents future research on sub-critical water.